Improving students' cognitive learning outcomes through quizizz learning media - Wismiati, Icha; Suzanti, Fitra; Daryanes, Febblina (Univeritas Papua, 2025)
Using a quasi-experiment design with a nonequivalent control group design, this study looks at how quizizz learning materials affect students' cognitive learning outcomes. It focuses on MIPA XI class students at a chosen SMAN in Dumai City, Riau. Purposive sampling is a method of sampling that incorporates specific selection criteria. Class XI MIPA 2 was the experimental group in this study, and class XI MIPA 3 was the control group. The experimental and control groups were given 25 multiple-choice questions as part of the research instrument during the pretest and posttest phases. The average posttest score for the experimental class increased to 7.22, according to statistical analysis. Using the t-test for hypothesis testing, the post-test score had a significance value of 0.034, which is less than 0.05. Additionally, the control class received an average N-gain value of 46.39%, indicating that it is less effective than the experimental class, which received an average N-gain value of 56.22%, indicating that it is quite effective. Therefore, it can be said that quizizz learning materials improve students' cognitive learning results.